INCOME OF SMALL-SCALE FISHERMAN IN COASTAL AREA - Meylin Rahmawati; Rizky Agusriyanti Irna; Sulistya Rini Pratiwi (Journal of Applied Economics in Developing Countries, 2022)
This research was conducted in the Lingkas Ujung Village which aims to determine the effect of fishermen's income on improving the economy of coastal communities in Tarakan City (Case Study: Lingkas Ujung Village). This study uses a quantitative descriptive approach, using simple linear regression to explain the influence between variables. Based on the results of the analysis it was found that fishermen's income had a positive and significant effect on improving the community's economy in Lingkas Ujung Village. The value of the coefficient of determination (R2) is 0.292, this indicates that there is a strong relationship between the fishermen's income variable and the increase in the community's economy.